Genotype–phenotype correlations in valosin-containing protein disease: a retrospective muticentre study. Issue 10 (27th July 2022) - Schiava, Marianela; Ikenaga, Chiseko; Villar-Quiles, Rocío Nur; Caballero-Ávila, Marta; Topf, Ana; Nishino, Ichizo; Kimonis, Virginia; Udd, Bjarne; Schoser, Benedikt; Zanoteli, Edmar; Souza, Paulo Victor Sgobbi; Tasca, Giorgio; et al.
Abstract : Background: Valosin-containing protein (VCP) disease, caused by mutations in the VCP gene, results in myopathy, Paget's disease of bone (PBD) and frontotemporal dementia (FTD). Natural history and genotype–phenotype correlation data are limited. This study characterises patients with mutations in VCP gene and investigates genotype–phenotype correlations. Methods: Descriptive retrospective international study collecting clinical and genetic data of patients with mutations in the VCP gene. Results: Two hundred and fifty-five patients (70.0% males) were included in the study. Mean age was 56.8±9.6 years and mean age of onset 45.6±9.3 years. Mean diagnostic delay was 7.7±6 years. Symmetric lower limb weakness was reported in 50% at onset progressing to generalised muscle weakness. Other common symptoms were ventilatory insufficiency 40.3%, PDB 28.2%, dysautonomia 21.4% and FTD 14.3%. Fifty-seven genetic variants were identified, 18 of these no previously reported. c.464G>A (p.Arg155His) was the most frequent variant, identified in the 28%. Full time wheelchair users accounted for 19.1% with a median time from disease onset to been wheelchair user of 8.5 years. Variant c.463C>T (p.Arg155Cys) showed an earlier onset (37.8±7.6 year) and a higher frequency of axial and upper limb weakness, scapular winging and cognitive impairment. Forced vital capacity (FVC) below 50% was as risk factor for being full-time wheelchair user, while FVC <70% and being a full-time wheelchair user were associated with death. Conclusion: This study expands the knowledge on the phenotypic presentation, natural history, genotype–phenotype correlations and risk factors for disease progression of VCP disease and is useful to improve the care provided to patient with this complex disease.